2020
DOI: 10.1002/em.22382
|View full text |Cite
|
Sign up to set email alerts
|

Promoter hypermethylation in CSF3R induces peripheral neutrophil reduction in benzene‐exposure poisoning

Abstract: Benzene is a global pollutant and has been established to cause leukemia. To better understand the role of DNA methylation in benzene toxicity, peripheral blood mononuclear cells were collected from six benzene-poisoning patients and six matched controls for genome-wide DNA methylation screening by Illumina Infinium Methylation 450 BeadChip. The Gene Chip Human Gene 2.0 ST Array (Affymetrix) was used to analyze global mRNA expression. Compared with the corresponding sites of controls, 442 sites in patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Wang et al ( 16 ) studied mitochondrial DNA methylation, specifically at the Mitochondrially Encoded Cytochrome c Oxidase I ( MT-COI ) gene, and reported two interesting results: mitochondrial methylation was lower in the exposed group; and methylation of MT-COI was correlated with white blood cell count and also with platelet levels. Epigenome-wide analysis was performed on a large scale for the first time by Ren et al ( 17 ), using the Infinium 450K methylation microarray. They reported 442 sites in benzene-exposed participants were hypermethylated, corresponding to 253 genes, and 237 sites were hypomethylated, corresponding to 130 genes.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al ( 16 ) studied mitochondrial DNA methylation, specifically at the Mitochondrially Encoded Cytochrome c Oxidase I ( MT-COI ) gene, and reported two interesting results: mitochondrial methylation was lower in the exposed group; and methylation of MT-COI was correlated with white blood cell count and also with platelet levels. Epigenome-wide analysis was performed on a large scale for the first time by Ren et al ( 17 ), using the Infinium 450K methylation microarray. They reported 442 sites in benzene-exposed participants were hypermethylated, corresponding to 253 genes, and 237 sites were hypomethylated, corresponding to 130 genes.…”
Section: Resultsmentioning
confidence: 99%
“…These key genes had potential regulatory effects on granulocyte proliferation and differentiation, immune response, pro-inflammatory activity and immune checkpoint factors. [13,14] Previous studies have identified some biomarkers of PD, but have no immune-related biomarkers. Songyun Zhao et al [15] identified 3 cuprotosis-related genes ATP7A, SLC31A1, and DBT associated with immune cells or immune function in PD and more accurate for the diagnosis of Parkinson disease course.…”
Section: Discussionmentioning
confidence: 99%
“…CSF3R is a type 1 cytokine receptor that binds granulocyte CSF, a cytokine vital for granulocyte proliferation and differentiation [29]. Acquired nonsense and frameshift truncation variants in the cytoplasmic domain and activating missense variants in the membrane-proximal region of CSF3R are found in a majority of cases of chronic neutrophilic leukemia, atypical chronic myeloid leukemia, chronic myelomonocytic leukemia, and de-novo acute myeloid leukemia [30].…”
Section: Discussionmentioning
confidence: 99%